101 Fertility sparing treatment with levonorgestrel intrauterine device after complete macroscopic hysteroscopic resection for well differentiated early stage endometriod adenocarcinoma in young women. (18th September 2019) - Kaabia, O; Nourallah, G; Rym, Z; Aymen, L; Aymen, S; Mohamed, B; Hédi, K
Abstract : Objectives: To evaluate the efficacy of levonorgestrel-intrauterine DEVICE (LNG-IUD) treatment after complete macroscopic hysteroscopic resection of well differenciated early-stage endometrioid carcinoma (EC) in young women who wished to preserve their fertility. Methods: A retrospective study from a prospective monocentric database was conducted from January 2008 to January 2019. Patients under 45 year old with grade 1 endometrioid adenocarcinoma confined to the endometrium were treated with LNG-IUD after complete macroscopic hysteroscopic resection. At 6 months of treatment, the histologic change of the endometrial tissue was assessed by both vaginal ultrasound and hysteroscopy with curettage. The regression rate at 6 months treatment was evaluated. Results: From a cohort of 226 patients with endometrial cancer diagnosed at our department during the 11 years of the study, 22 were under 45 year old of whom nine patients with FIGO Stage IA grade 1 endometroid carcinoma were enrolled in this study. Two withdrew because they were pregnant at the moment of diagnosis of the cancer and 9 patients completed the protocol treatment. The complete regression (CR) rate at 6 months was 33.3% (3/9). There were 2 cases of progressive disease. Five patients reported some spotting as a treatment-related complication. Conclusions: The need for a fertility spearing treatment to early stage grade 1 endometrioid carcinoma in young women is real but not so frequent in our daily practice. LNG-IUD treatment in addition to complete macroscopic hysteroscopic resection for EC showed 33.3% of CR rate at 6 months with a progression rate of 22.2%.